Paravortex panopea n. sp. (Platyhelminthes: Rhabdocoela) on clams from the northern Patagonian coast, Argentina: Pathogeny and specificity - Brusa, Francisco (2011)
During a histopathological survey of the geoduck, Panopeaabbreviata (Hiatellidae), and the razor clam, Ensis macha (Pharidae), in northern Patagonian gulfs (Argentina), turbellarian worms were found in the intestine lumen. In this work, we described a new species of Paravortex (Platyhelminthes, Graffillidae). We collected the hosts by scuba diving and dissected alive for studying the turbellarians. In this new species, the pharynx continues in a short esophagus and the latter in a saccular intestine. Gravid specimens have from 2 to 8 twin embryos in the parenchyma. A short penis papilla arises from the seminal vesicle and the gonopore presents a strong sphincter. This species resembled P. nicolli Szidat, 1965, which was described paraziting Mytilus edulis platensis in Buenos Aires, Argentina. The new species can be differentiated from P. nicolli mainly by the presence of a penis papilla and a sphincter between genital atrium and gonopore. This turbellarian species was significantly more prevalent in geoducks (28 %, n = 210) than in razor clams (6 %, n = 480) (KW, p < 0.0001). For both host species, no evidence of direct physical damage caused by turbellarians was observed.